Hydrogeologic characterization of an alpine glacial till, Snowy Range, Wyoming - Houghton, Tyler B., author; Ronayne, Michael, advisor; Stednick, John, committee member; Sanford, William, committee member (Colorado State University. Libraries, 2011)
Characterization of sediment hydraulic properties is essential to understanding groundwater movement. In many mountain watersheds, surficial geologic material, such as glacial till, plays an important role in water and nutrient chemical cycling. Hydraulic properties of alpine glacial tills are infrequently measured, requiring efforts to characterize this complex geologic material. This research involved the use of multiple measurement techniques to determine the saturated hydraulic conductivity of surficial glacial tills at the Glacier Lakes Ecosystem Experiments Site (GLEES) in south-central Wyoming. During the summer of 2010, three in situ methods (double-ring infiltrometer, mini disk infiltrometer, and Guelph permeameter) were used to measure field-saturated hydraulic conductivity (K sat) at 32 locations around GLEES. Estimated K sat values obtained with the double-ring infiltrometer had a geometric mean of 0.12 cm/min and range of 0.007 to 0.40 cm/min. The Guelph permeameter had a geometric mean of 0.094 cm/min and range of 0.003 cm/min to 0.776 cm/min, and the mini disk infiltrometer obtained estimates with a geometric mean of 0.014 cm/min and ranged from 0.002 cm/min to 0.043 cm/min. The double-ring infiltrometer and Guelph permeameter measure K sat at a physical scale that is large enough to incorporate the large mixture of particle sizes that comprise the till. With a smaller physical measurement scale, the mini disk is predominantly influenced by the fine-grained fraction of the till. Using geometric mean K sat values obtained with the double-ring and mini disk infiltrometers and available snowpack data from the 2005 water year, a physically-based hydrologic and energy-balance model was used to simulate snowpack depletion, soil moisture changes, and groundwater recharge. Simulated sediment moisture changes were used to estimate vertical flow rates toward the water table. Using a higher K sat obtained at a larger physical measurement scale, the calculated flow rate 2 m below the surface is approximately three times that of the low K sat scenarios. Thus, the scale dependency of hydraulic conductivity is important when quantifying groundwater recharge in mountain watersheds.
Keywords: hydrogeologic characterization; scale dependency; mountain watershed; infiltration tests; glacial till; hydraulic conductivity